2011
DOI: 10.1175/2010jpo4253.1
|View full text |Cite
|
Sign up to set email alerts
|

Mixing in the Transition Layer during Two Storm Events

Abstract: Upper-ocean dynamics analyzed from mooring-array observations are contrasted between two storms of comparable magnitude. Particular emphasis is put on the role of the transition layer, the strongly stratified layer between the well-mixed upper layer, and the deeper more weakly stratified region. The midlatitude autumn storms occurred within 20 days of each other and were measured at five moorings. In the first storm, the mixed layer follows a classical slab-layer response, with a steady deepening during the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 32 publications
(29 reference statements)
7
59
1
Order By: Relevance
“…The results documented in our study and those of other studies indicate that strong turbulent mixing occurs below the base of the mixed layer during the strong wind bursts (Grant and Belcher 2011;Dohan and Davis 2011). The magnitude of the enhanced mixing that is correlated with the near-inertial waves should be related to the energy flux that propagates from sea surface to the interior (Alford 2001).…”
Section: Introductionsupporting
confidence: 79%
“…The results documented in our study and those of other studies indicate that strong turbulent mixing occurs below the base of the mixed layer during the strong wind bursts (Grant and Belcher 2011;Dohan and Davis 2011). The magnitude of the enhanced mixing that is correlated with the near-inertial waves should be related to the energy flux that propagates from sea surface to the interior (Alford 2001).…”
Section: Introductionsupporting
confidence: 79%
“…While large-scale entrainment mixing causes the mixed layer to deepen and cool over the course of several days without affecting the temperature below the mixed layer, diffusive mixing (term 4 on RHS of (1)) causes a transport of heat from the mixed layer to the waters below. Diffusive mixing thus can cause cooling within the mixed layer and warming below, thus reducing the stratification of the upper ocean (e.g., at Station Papa: Large et al, [1986]; Large and Crawford, [1995]; Dohan and Davis, [2011]). …”
Section: Methodology and Datamentioning
confidence: 99%
“…The shear production term PðS 2 Þ is less than the shear evolution @S 2 @t in the transition layer, but the phases of the two terms are in good agreement throughout the time series. Unidirectional monsoon winds disallow the resonance between rotation of the wind and earths rotation which is the cause of amplification of near-inertial currents in midlatitudes [Dohan and Davis, 2011]. In the Arabian sea, the time variation of wind stress and rotation of the bulk shear across the transition layer (Figure 9, fourth plot) cause the increase in magnitude of the bulk shear across the transition layer when this shear and wind stress are aligned.…”
Section: Journal Of Geophysical Research: Oceansmentioning
confidence: 99%
“…Several studies in the midlatitudes [Alford et al, 2012;Dohan and Davis, 2011] document the evolution of near inertial currents that are generated mostly by short-duration storms and by rotating winds. Alternatively, Weller et al [2014] found strong near-inertial currents generated by accelerating and decelerating wind stress in the unidirectional trade wind regime in the southeast Pacific.…”
Section: 1002/2014jc010198mentioning
confidence: 99%